Water resources management : technical paper ([O.A.S.] WashingtonUS, 1996)
Suggests that in order to maintain and build on the commitments of Governments of the Americas to sustainable water resources management the following initiatives should be implemented - strengthen and coordinate water policies; address transboundary water issues; and, promote networks for water information exchange.
DC